2008
DOI: 10.1021/tx8000175
|View full text |Cite
|
Sign up to set email alerts
|

Semiquinone Radicals from Oxygenated Polychlorinated Biphenyls: Electron Paramagnetic Resonance Studies

Abstract: Polychlorinated biphenyls (PCBs) can be oxygenated to form very reactive hydroquinone and quinone products. A guiding hypothesis in the PCB research community is that some of the detrimental health effects of some PCBs are a consequence of these oxygenated forms undergoing one-electron oxidation or reduction, generating semiquinone radicals (SQ•−). These radicals can enter into a futile redox cycle resulting in the formation of reactive oxygen species, that is, superoxide and hydrogen peroxide. Here, we examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
127
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 85 publications
(138 citation statements)
references
References 47 publications
11
127
0
Order By: Relevance
“…However, the max of the initial species was higher than expected for a quinone (35). Its transient nature and the susceptibility of quinones to undergo comproportionation (30) in the presence of their reduced counterparts (i.e. hydroquinones and catechols) suggested that the pink species was a radical (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the max of the initial species was higher than expected for a quinone (35). Its transient nature and the susceptibility of quinones to undergo comproportionation (30) in the presence of their reduced counterparts (i.e. hydroquinones and catechols) suggested that the pink species was a radical (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…DOPAL Auto-oxidation and ROS Production-Superoxide formation during DOPAL auto-oxidation was investigated using the method of Eyer (30,33). UV-visible spectrophotometry (kinetic settings) was used to measure the change in absorbance at 400 nm during auto-oxidation of DOPAL (0.5 mM) in 50 mM NaH 2 PO 4 , pH 7.8.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…6b). HT-quinone may interact with HT in a comproportionation reaction to generate more semiquinone radicals (Song and Buettner 2010;Song et al 2008;Song et al 2009). This redox cycle of HT could elicit an oxidative stress response and cells may adapt to this oxidative insult by promoting their antioxidant defense system.…”
Section: Discussionmentioning
confidence: 99%
“…6a). Semiquinone radicals are the primary source for formation of superoxide from the hydroquinonesemiquinone-quinone triad (Eyer 1991;Song and Buettner 2010;Song et al 2008;Venkatesha et al 2008). If superoxide is formed in the oxidation of hydroquinones that have relatively high redox potentials, then superoxide dismutase will accelerate the oxidation of hydroquinone, forming quinone.…”
Section: Sodium Cyanide Was Used To Distinguish Between Mnsod and Cuzmentioning
confidence: 99%